Effect of thermal residual stress on the tensile properties and damage process of C/SiC composites at high temperatures. Issue 3 (1st February 2022) - Zhang, Qi; Ge, Jingran; Zhang, Binbin; He, Chunwang; Wu, Zhenqiang; Liang, Jun
Abstract: Due to the mismatch of the thermal expansion coefficients between the matrix and yarns, thermal residual stress will appear in C/SiC composites. In this paper, a progressive damage model was used to predict the thermal-mechanical behavior of C/SiC composites and reveal the failure mechanism. Firstly, the properties of the composites under tensile load were tested at three different temperatures in vacuum. Then, the elastic-plastic progressive damage constitutive laws were used and implemented by a user-defined subroutine UMAT in ABAQUS. The thermal residual stress evolution in the cooling and heating processes was characterized. Finally, the stress-strain curves of the composites under tensile load at different temperatures were studied. The effects of thermal residual stress on the tensile properties and progressive damage process of C/SiC composites were revealed sequentially. This work can give design guidance for strengthening of C/SiC composites.